Treinamento de profissionais para aplicação de um recurso informatizado e aquisição de leitura e escrita por pessoas com autismo em contexto clínico - Pinto, Giovana Zanardo Costa (Universidade Federal de São Carlos, 2025)
Teaching reading and writing is essential for individuals living in society. People with autism may face challenges in interpretation, word-meaning association, and literal understanding, making it essential for the teaching of these skills to be planned and structured through evidence-based practices. The computerized teaching program "Learning to Read and Write in Small Steps" (ALEPP), based on the Stimulus Equivalence paradigm, has been employed in various contexts by different agents and has demonstrated positive outcomes across diverse audiences. Training agents to implement evidence-based instructional resources is critical to ensuring the fidelity of teaching program implementation. This study aimed to evaluate whether the training provided to professionals was sufficient to ensure the proper application of the program and the effective monitoring of learners during tasks, thus assessing the effects of the ALEPP program on individuals with autism in a clinical setting. The study was conducted in a private behavioral intervention clinic located in the interior of São Paulo, Brazil. Four participants with autism, aged between 6 and 11 years (one girl and three boys), were selected alongside seven instructors, who participated in an initial training program. This training included theoretical instructions on the stimulus equivalence paradigm, modeling of the program’s use, and practical simulations. The dependent variables included instructor’s performance in program implementation, assessed through application simulations, checklist records, and session monitoring, as well as the learners’ performance in reading and writing tasks, measured by the number of correct responses in ALEPP activities and the Reading and Writing Diagnosis (DLE) assessment. The teaching program was implemented through a baseline phase to assess the learners’ initial repertoires, the application of the ALEPP program, and follow-up meetings with instructors for adjustments and support. The results showed that the initial training was sufficient to ensure the proper application of the program in most situations. However, in some cases, additional feedback and practical support were necessary to adjust teaching strategies. Regarding learner performance, the results indicated that all four participants significantly expanded their reading and writing repertoires after the application of the ALEPP program. However, environmental adjustments, such as the introduction of reinforcement schedules, modifications to the physical application setting, and solutions to technical issues, were required. Social validity data, obtained through questionnaires administered to the learners, their caregivers, and instructors, demonstrated that the implementation of the program in the clinical setting was effective, contributed to teaching programming, and facilitated participation in activities related to reading and writing skills in other contexts during after-school hours.
Training professionals for the application of a computerized resource and the acquisition of reading and writing skills by people with autism in a clinical setting
Keywords: Educação Especial; Programa Informatizado; Autismo; Profissionais Clínicos; CIENCIAS HUMANAS::EDUCACAO; 4. Educação de Qualidade